Noninducible Tet repressor mutations map from the operator binding motif to the C terminus. - Hecht, B (1993)
We have developed a new genetic selection system for Tet repressor mutations with a noninducible phenotype for tetracycline (TetRs). Extensive chemical mutagenesis of tetR yielded 93 single-site Tet repressor mutations. They map from residue 23 preceding the alpha-helix-turn-alpha-helix operator binding motif to residue 196 close to the C terminus of the repressor. Thirty-three of the mutations are clustered between residues 95 and 117, and another 27 are clustered between residues 131 to 158. Several of the mutants were characterized quantitatively in vivo for induction by tetracycline and anhydrotetracycline. While all of these are severely reduced in tetracycline-mediated induction, only some of them are affected for anhydrotetracycline-mediated induction.